1981
DOI: 10.1093/bja/53.12.1273
|View full text |Cite
|
Sign up to set email alerts
|

Glycopyrrolate in Children

Abstract: The effects of glycopyrrolate 10 microgram kg-1 i.v. given at induction of anaesthesia were compared with those of atropine 20 microgram kg-1 i.v. given at induction and oral atropine 30 microgram kg-1 given 90 min before operation. Antisialagogue effect, changes in axillary temperature, heart rate, frequency of cardiac arrhythmia and postoperative restlessness were determined. Patients who had received oral atropine had more pharyngeal secretions, a lower heart rate and a greater frequency of cardiac arrhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…glycopyrrolate is identical. 17 Our results were similar to that study. Sigurdsson and colleagues reported that in children, the incidence of ventricular arrhythmias is increased after diazepam-atropine premedication, compared with that after diazepam-morphinehyoscine.…”
Section: Discussionsupporting
confidence: 92%
“…glycopyrrolate is identical. 17 Our results were similar to that study. Sigurdsson and colleagues reported that in children, the incidence of ventricular arrhythmias is increased after diazepam-atropine premedication, compared with that after diazepam-morphinehyoscine.…”
Section: Discussionsupporting
confidence: 92%
“…Malling et al ( Malling et al, 1988 ) compared the combination of glycopyrrolate and atropine with neostigmine to antagonize residual muscle relaxation during hip arthroplasty in elderly patients undergoing general anesthesia and found no difference in postoperative awakening time between the two groups. In this trial, although one case of postarousal agitation occurred in group A (glycopyrrolate), no significant difference was observed in the overall time to arousal or quality of arousal between the two groups, thus further confirming the findings of Malling ( Malling et al, 1988 ) et al In addition, the doses of both glycopyrrolate and atropine were relatively conserved in our experiment, and no significant effects on the patients’ body temperature were found, similar to the findings of Warran et al ( Warran et al, 1981 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite several studies comparing the anti-salivary effects of glycopyrrolate and atropine, no consistent conclusions have been reached. For instance, Warran et al ( Warran et al, 1981 ) compared the oropharyngeal secretions (defined as oropharyngeal “moist” or “dry” depending on whether aspiration was required) during tracheal intubation, intraoperatively, and postoperatively in three groups that were given atropine (i.v), atropine (i.m) and glycopyrrolate (i.v) before anesthesia induction in children undergoing tonsillectomy and adenoidectomy. The results showed that there was no difference in oropharyngeal dryness at the time of intubation or in the postoperative period; however, glycopyrrolate was better at inhibiting gland secretion during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Warran et al compared the effects of intravenous injection of atropine or glycopyrrolate prior to induction of anesthesia with those of preoperative oral atropine on oropharyngeal secretions after completion of general tracheal intubation, during and after surgery in children (de ned as oropharyngeal "moist" or "dry" by whether aspiration was required). The results did not differ between the three groups in terms of oropharyngeal dryness at the time of intubation and postoperatively, and the intraoperative effect of glycopyrrolate in inhibiting glandular secretion was better [25] . Lavis et al compared the effects of glycopyrrolate with atropine as a preoperative medication in children undergoing tonsillectomy and adenoidectomy and found no difference in the duration of postoperative dry mouth between the two groups [26] .Black et al compared the effects of glycopyrrolate and atropine in combination with neostigmine in children for muscarinic antagonism, de ning oropharyngeal conditions as 'dry', 'moist' and 'unacceptably moist', and found that although there was no statistical difference in the anti-salivary effect of the two drugs, the attending anesthetist subjectively felt that glycopyrrolate was more effective [27] .…”
Section: Discussionmentioning
confidence: 74%